Kualitas Pelayanan dan Fasilitas serta Pengaruhnya terhadap Kepuasan Konsumen pada M2M Indonesian Fast Food Cabang Pahlawan Mojokerto - Imam Wahyudi (FADZAT: Jurnal Ekonomi Syariah, 2021)
The purpose of this study was to analyze the simultaneous, partial and dominant effect of the variable quality of service and facilities on consumer satisfaction. This research is explanatory (explaining) is "to test the hypotheses of a cause-and-effect relationship between the symptoms (variables) being studied. The type of data used is the type of quantitative data which is quantified using a Likert scale. The research population is the users of Indonesian Fast Food M2M Delivery Service at Pahlawan Mojokerto branch. Data analysis used multiple linear regression. The results showed that: 1) Service quality and facilities had a simultaneous effect on consumer satisfaction. 2) Quality of service and facilities have a partial effect on consumer satisfaction. 3) Facilities have a dominant effect on consumer satisfaction. Limitations of the study: 1) The population of this study was conducted at M2M Indonesian Fast Food, Pahlawan Mojokerto branch. 2) The population and sample consisted of 200 users of the Indonesian Fast Food M2M Delivery Service at the Pahlawan Mojokerto branch. 3) Data collection is carried out on December 23, 2020 until. January 30, 2021.